Autostable-II stent versus bicanalicular silicon intubation for management of lacrimal canalicular obstruction - Zamzam M.A. Khalil; Raafat M.A. Abdallah; Ahmed M.K. Elshafei; Amr A.M. Abdelrahman (Journal of the Egyptian Ophthalmological Society)
Purpose To compare the anatomical and functional results of the use of Autostable-II self-retaining stent (A-II SRS) and bicanalicular silicone tube (BST) in the treatment of epiphora due to distal or common canalicular obstruction. Setting and design This prospective, comparative, interventional study was conducted at El Minia University, Faculty of Medicine, Department of Ophthalmology. Patients and methods This study included 80 eyes of 65 patients and was performed from March 2020 to June 2021 in Minia University Hospital. Detailed history taking, anterior segment examination, lacrimal probing, and syringing were done. The patients were evaluated 1 day, 1 week, 1 month, and 3 months postoperatively when A-II SRS and BST were removed and 3 months after their removal. Results Eighty eyes of 56 patients with distal canalicular obstruction were evaluated in this study. Patients in group A were treated using A-II SRS (FCI), and patients in group B were treated by BST (EAGLE LABS). Results revealed a highly statistically significant difference between the two groups in epiphora grading 1 day postoperatively (P=0.013) and no significant difference between the two groups postoperatively at 1 week, 1 month, 3 months, and 6 months. Objective improvement indicated by fluorescein dye disappearance test by the end of the follow-up period revealed no significant difference between the two studied groups (P=0.39). Regarding tube position, in group A, two (5%) stents were extruded. In group B, only one (2.5%) was prolapsed and removed by the end of the first month. Conclusion The advantage of A-II SRS set over BST intubation surgery for lacrimal canalicular obstruction is easy placement without general anesthesia. However, extra costs are needed for A-II SRS, which is an important issue in areas with low economic income.